(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Publication metrics indicate the visibility and reach of a research publication. The metrics can be at article-level, author-level, and journal-level to measure the scholarly output and its impact. Bibliometrics is the use of statistical methods to analyze various publications mostly used in the field of library and information science; whereas, scientometrics is the sub-field concerned with the science of metrics for the measurement and analysis of scholarly publications. Readers are not always well informed about the various publication metrics, and use them without knowing how to interpret them, their strength and limitations.